Sclerostin's role in bone–muscle crosstalk and osteoporosis pathogenesis - Shahid, Hamzah; Morya, Vivek Kumar; Noh, Kyu-Cheol (Osteoporosis and Sarcopenia, 2025)
This review examines sclerostin, a critical regulator of Wnt signaling, focusing on its role in bone homeostasis and its emerging involvement in muscle–bone crosstalk. It examines the regulatory influence of hormones, mechanical stress, and myokines on sclerostin expression under both physiological and pathological conditions. Recent advances underscore sclerostin's role in osteoporosis pathogenesis and its involvement in bone remodeling, while also revealing its emerging significance in muscle–bone communication. Despite these insights, the underlying mechanisms of its regulation remain incompletely understood. By consolidating recent research, this review provides a comprehensive perspective on sclerostin's multifaceted roles and their implications for bone and muscle health.